Impact of Artificial Intelligence on Content Marketing in the Context of Bangladesh - Omar Faruk (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to examine the impact of artificial intelligence (AI) on the content marketing job sector in Bangladesh. The study involved surveying 65 content marketers from various sectors. Primary data analysis was performed using SPSS software and Microsoft Excel. The results revealed that most of the participants believed that AI has positively impacted the content marketing sector by increasing efficiency and saving time, while a significant relationship was found between content types and AI tools, indicating a preference for automated content generation among blog and video content creators. Overall, the findings suggest that AI has a significant influence on content marketing in Bangladesh. While some content creators perceive positive impacts, others express concerns about job security and the need for training to cope with AI technology.